Plasmonic enhancement of the magneto-optical response of MnP nanoclusters embedded in GaP epilayers - Monette, Gabriel; Nateghi, Nima; Masut, Remo A.; Francoeur, Sébastien; Ménard, David (Physical review. B, Condensed matter and materials physics, 2012)
We report on the magneto-optical activity of MnP nanoclusters embedded in GaP epilayers and MnP thin film as a function of temperature, magnetic field, and wavelength in the near infrared and visible. The measured Faraday rotation originates from the ferromagnetic magnetization of the metallic MnP phase and exhibits a hysteretic behavior as a function of an externally applied magnetic field closely matching that of the magnetization. The Faraday rotation spectrum of MnP shows a magnetoplasmonic resonance whose energy depends on the MnP filling factor and surrounding matrix permittivity. At resonance, the measured rotary power for the epilayer systems increases by a factor of 2 compared to that of the MnP film in terms of degrees of rotation per MnP thickness for an applied magnetic field of 410 mT. We propose an effective medium model, which qualitatively reproduces the Faraday rotation and the magnetocircular dichroism spectra, quantitatively determines the spectral shift induced by variations in the MnP volume fraction, and demonstrates the influence of the shape and orientation distributions of ellipsoidal MnP nanoclusters on the magneto-optical activity and absorption spectra.